Banned Birds The Birds of Leviticus 11 and Deuteronomy 14 - Altmann, Peter (Archaeology and Bible, 2019)
The dietary prohibitions in Leviticus 11 and Deuteronomy 14 represent one of the most detailed textual overlaps in the Pentateuch between the Priestly material and Deuteronomy. This is especially the case for the birds: their identities are shrouded in mystery and the reasons for their prohibition debated. Peter Altmann attempts to break this impasse by setting these flyers within the broader context of birds and flying creatures in the Ancient Near East. His investigation considers the zooarcheological data on birds in the ancient Levant, iconographic and textual material on mundane and mythic flyers from Egypt and Mesopotamia, as well as studying the symbolic functions of birds within the texts of the Hebrew Bible itself.